The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3102/0091732x17690120
|View full text |Cite
|
Sign up to set email alerts
|

Combating Inequalities in Two-Way Language Immersion Programs: Toward Critical Consciousness in Bilingual Education Spaces

Abstract: This chapter reviews critical areas of research on issues of equity/equality in the highly proclaimed and exponentially growing model of bilingual education: two-way immersion (TWI). There is increasing evidence that TWI programs are not living up to their ideal to provide equal access to educational opportunity for transnational emergent bilingual students. Through a synthesis of research from related fields, we will offer guidelines for program design that attend to equality and a framework for future resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
124
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 301 publications
(133 citation statements)
references
References 102 publications
(162 reference statements)
1
124
0
2
Order By: Relevance
“…Despite these federal mandates, however, schools continue to have difficulties involving, engaging, and thus, building relationships with families (Moles & Fege, 2011;Nevin, 2008). Moreover, certain educational programs, such as language immersion schools, may not have policies in place that allow them to serve their entire population, most specifically the minoritized children that they are created to serve (Cervantes-Soon, Dorner, et al, 2017;Dorner, 2011;Valdés, 1997).…”
Section: Discussion: Parent Engagement As Discursive Powermentioning
confidence: 99%
See 4 more Smart Citations
“…Despite these federal mandates, however, schools continue to have difficulties involving, engaging, and thus, building relationships with families (Moles & Fege, 2011;Nevin, 2008). Moreover, certain educational programs, such as language immersion schools, may not have policies in place that allow them to serve their entire population, most specifically the minoritized children that they are created to serve (Cervantes-Soon, Dorner, et al, 2017;Dorner, 2011;Valdés, 1997).…”
Section: Discussion: Parent Engagement As Discursive Powermentioning
confidence: 99%
“…Contrary to expectations and hopes, the extant research on the climate of language immersion schools has found that they often benefit English-speaking students and families, rather than speakers of other languages (Cervantes-Soon, Dorner, et al, 2017;Flores, 2010;Valdés, 1997). Families' perceptions of school climate-including barriers such as lack of communication, collaborative efforts, and trust-may make it difficult for parents of immigrant and minoritized language backgrounds to develop partnerships with their children's schools, even in language immersion schools that presumably are designed to work with cultural and linguistic diversity (Dorner, 2010;Kavanagh, 2014;Lee & Bowen, 2006).…”
Section: School Climate and Parent Engagement In Language Immersion Pmentioning
confidence: 99%
See 3 more Smart Citations